Navigating multiple languages: The use and effect of code-switching in children from mixed marriage families - Annisa Rahmadani (Universitas Pendidikan Indonesia, 2023)
The phenomenon of code-switching manifests as the practice of seamlessly oscillating between two or more distinct languages or language variations within the confines of a singular exchange, be it a sentence or a conversation. Children reared in environments rich with linguistic diversity frequently acquire the ability to proficiently maneuver between languages as a mechanism to convey meaning to varied interlocutors or within disparate situational contexts. This study presents a qualitative case study of two children from mixed marriage parents, one of whom is an Indonesian native speaker and the other is an English native speaker. The aim of the study is to explore the use of code-switching and its impact on the language development and proficiency of children from mixed-marriage families. Interviews were conducted with the parents, while observations were made of the children's language use at home.Â The results suggest that code-switching facilitates the development of children's language skills in different contexts; however, it also hinders their ability to separate and utilize different languages effectively. Furthermore, code-switching enables children to maintain a connection to their cultural heritage and fosters a sense of comfort in multicultural environments.Â